2019
DOI: 10.1029/2018ja026367
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Solar Irradiance Effects in the Mesosphere

Abstract: We investigate trends and solar irradiance effects in the mesosphere using the Whole Atmosphere Community Climate Model with eXtended thermosphere and ionosphere (WACCM‐X) and radar measurements of winds at Collm (51°N, 13°E), for the period of 1980–2014. We found that in the mesosphere, dynamics significantly impact temperature and wind trends, as well as how solar irradiance affects the temperature and winds. The global average temperature trends are negative, with a maximum of ~−1 K per decade in the middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 90 publications
6
56
1
Order By: Relevance
“…, which substantiates the uncertainties regarding this complex atmospheric region. Other model estimates, includingAkmaev and Fomichev (2000),Fomichev et al (2007),Garcia et al (2007),Lübken et al (2013), andQian et al (2019) are in general agreement with the WACCM-X simulations, finding mesopause-region trends to be fairly small.…”
supporting
confidence: 70%
“…, which substantiates the uncertainties regarding this complex atmospheric region. Other model estimates, includingAkmaev and Fomichev (2000),Fomichev et al (2007),Garcia et al (2007),Lübken et al (2013), andQian et al (2019) are in general agreement with the WACCM-X simulations, finding mesopause-region trends to be fairly small.…”
supporting
confidence: 70%
“…The temperature response is significant in the upper mesosphere during July and January (Figures a and b), with the exception of a slightly reduced solar response at the highest latitudes in summer. Model studies (Gan et al, ; Karlsson & Kuilman, ; Qian et al, ) have shown a far stronger reduction in the T‐Lα correlation near the polar summer mesopause than is indicated by the observations in Figure , a discrepancy that is currently not understood. The H 2 O‐Lα anticorrelation is significant in the upper mesosphere during July and January (Figures c and d), except for latitudes poleward of ~55° where a weak positive correlation appears.…”
Section: The Missing Solar Cycle Responsementioning
confidence: 86%
“…The mystery deepens as some models predict a strong solar cycle response in PMCs, T, and H 2 O after 1979 (e.g., Berger & Lübken, ; Lübken et al, , ), while others indicate a missing solar cycle response in T near the polar summer mesopause (Gan et al, ; Karlsson & Kuilman, ; Qian et al, ). Hartogh et al () showed that the anticorrelation between solar Lyman‐α (Lα) and H 2 O measured in the polar upper mesosphere was present in winter but not summer (1996–2006 at 69°N).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing eddy diffusion was advanced as a possible explanation of increasing CO2 trends with altitude (Emmert et al, 2012). However, Qian et al (2019) have shown that sampling of SABER data in window lengths less than 60 days can lead to incorrect CO2 values. As a result, increased eddy diffusion is no longer necessary to explain the anomalous CO2 https://doi.org/10.5194/acp-2019-1097 Preprint.…”
Section: Mechanisms For a 4 Year Cyclementioning
confidence: 99%